Pengaruh Sosial Media, Niat Beli Terhadap Keputusan Pembelian Produk Ramah Lingkungan The Body Shop - Mayuni, Nadia Putri; Sumiati, Sumiati (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2025)
The purpose of this research is to examine the influence of social media, purchase intentions on purchasing decisions for environmentally friendly products at The Body Shop (Grand Basko Mall, Padang City). The variables used in this research include the dependent variable, namely purchase decision (Y) and the independent variables, social media (X1) and purchase intention (X2). This type of research uses quantitative methods, collecting data by distributing questionnaires to 77 respondents using accidental sampling techniques. By using instrument tests (validity test, reliability test and level of respondent achievement), assumption tests (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression and hypothesis testing with the help of the SPSS application. The results of this research show that social media does not have a significant influence on the decision to purchase The Body Shop products, purchase intention shows that it has a positive and significant influence on the decision to purchase The Body Shop products, then social media and purchase intention have a positive and significant influence on the decision to purchase the product. The Body Shop.